Doctors and managers: poor relationships may be damaging patients—what can be done?. (26th November 2003) - Edwards, N
Abstract : The problem of poor relationships between doctors and managers is a common feature of many healthcare systems. This problem needs to be explicitly addressed and there are a number of positive steps that could be taken. Firstly, there would be value in working to improve the quality of relationships and better mutual understanding of the necessarily different positions of doctors and managers. Finding a common approach to managing resources, accountability, autonomy, and the creation of more systematic ways of working seems to be important. The use of costed clinical pathways may be one approach. Rather than seeing guidelines and accountability systems as a threat to autonomy there is an argument that they are an essential adjunct to it. Redefining autonomy in order to preserve it and to ensure that it encompasses accountability and responsibility will be an important step. A key step is the development of clinical leadership.